Development of Digital Comics Based on Local Wisdom to Improve Students' Mathematical Literacy Skills - Sari, Indah Puspita; Supriyadi, Edi; Hidayat, Wahyu (Universitas Muhammadiyah Mataram, 2025)
This study aims to develop a digital comic based on local wisdom to enhance the mathematical literacy skills of junior high school students. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques included both test and non-test instruments. The test instrument comprised a mathematical literacy assessment designed to measure students’ mathematical literacy skills, while the non-test instruments included observation sheets, interview guidelines, student response questionnaires toward the digital comic, and validation sheets to assess the practicality and validity of the developed product. The validity and practicality data were analyzed using percentage techniques, while the effectiveness of the product was evaluated using the N-gain score. The findings indicate that the digital comic based on local wisdom achieved content and graphic component validity scores of 75.67% and 76.33%, respectively, categorized as “valid.” Meanwhile, the presentation and language components received validity scores of 66.67% and 68.33%, categorized as “moderately valid.” In terms of ease of use, visual appeal, and perceived usefulness, the instructional material was deemed “highly practical.” Test results revealed that students’ scores across all mathematical literacy indicators fell within the moderate category. Based on these findings, it can be concluded that the developed digital comic grounded in local wisdom is valid, practical, and effective for use in classroom instruction to enhance students’ mathematical literacy. From a practical standpoint, this comic offers an engaging alternative for contextual learning media. Academically, the results underscore the importance of integrating local culture and visual media in the development of innovative instructional materials.